PEWARNAAN PELANGI DAN PEWARNAAN ANTIAJAIB PELANGI PADA GRAF SLINKY Sl_n C_4 - I Kadek Agi Redityawan; Putu Kartika Dewi; Raphita Yanisari Silalahi (Ikatan Dosen Menulis, 2026)
Rainbow coloring and rainbow antimagic coloring are developoing topics in graph theory bcause they combine the concepts of rainbow connectivity and antimagic labeling. this study aims to determine the rainbow connection number and the rainbow antimagic connection number of slinky graph (Sl_n C_4 ) for n≥2. This research employs a contructive approach by constructing rainbow antimagic coloring based on observed patterns. Furthermore, the existence of a rainbow path for every pair of vertices is verified. The results show that the rainbow connection number of the slinky graph (Sl_n C_4 ) is rc(Sl_n C_4 )=2n. In addition, upper bounds for the rainbow antimagic connection number ar obtained, namely 4≤rac(Sl_n C_4 )≤5 for n=2, and 2n≤rac(Sl_n C_4 )≤⌊(5n+5)/2 ⌋, for n≥3.